Pembagian Waris di Minangkabau Menurut Hukum Ekonomi Syari’ah (Studi Kasus di Keluarga Besar Sungai Batang Tanjung Sani Kabupaten Agam di Bandar Lampung) - Maskar, Garyani (Bayani, 2023)
This article describes the review of inheritance in an Islamic perspective. In Islamic law, the division of inheritance (faraidh) is part of a problem that has clear rules. Inheritance is a matter of what and how various rights and obligations regarding a person's wealth when he dies will be transferred to the living family. This distribution of inheritance is usually distributed more to men than women, but this is contrary to the distribution of inheritance in Minangkabau custom which gives more inheritance to daughters compared to inheritance to sons, besides that in Minangkabau custom divided into two inheritance rights namely high inheritance and low inheritance. To be more in-depth about the understanding of inheritance, the authors approach it through the hadith of inheritance. Therefore, the purpose of this research is to examine the distribution of inheritance in Minangkabau according to Islamic economic law, seen through the hadith. the author uses qualitative methods. This research is classified as library research, which examines the main problem through the literature or references related to the title of this research.